Moisture Stress Effects at Different Phenophases in Four Groundnut (Arachis Hypogaea L.) Cuitivars - Babu, V Ramesh; Murty, P S.S; Reddy, D Narasimha (Annals of Arid Zone, 2016)
Spanish bunch groundnut cultivars (TMV 2, J 11, DH 3-30 and Jyoti) regulate vegetative growth under moisture stress and exhibit higher rates of leaf area expansion and biomass production upon alleviation of stress. They however, show continued loss of ground cover and biomass production when stressed beyond early pod development phase. No significant variability was observed amongst the four cultivars in the above features. Results indicate that soil moisture stress during the vegetative, flowering, pegging and early pod development caused no significant losses in yields. On the other hand plants with adequate water supply in the above phases that were exposed to stress in their late pod development and pod maturation periods showed significant reduction of yields.